A new transboundary freshwater dispute before the International Court of Justice. Issue 1 (2nd January 2017) - Meshel, Tamar
ABSTRACT: On 6 June 2016 Chile submitted its long-standing dispute with Bolivia concerning the Silala/Siloli watercourse to the International Court of Justice. Since 1997 Bolivia has contended that the watercourse is not international and that it therefore belongs exclusively to Bolivia. In its application, Chile requested that the court "declare that the Silala River system is in fact and in law an international watercourse whose use by Chile and Bolivia is governed by customary international law". This case has the potential to produce a landmark decision in the international water law field since it is the first time that a dispute concerning the status of a watercourse as international has been submitted to the court. If the court finds that the Silala/Siloli is indeed an international watercourse, it will have a unique opportunity to clarify states' substantive and procedural obligations with respect to its use.